Contribution to the ethnobotanical study of antidiabetic medicinal plants of the Central Middle Atlas region (Morocco) - Hachi, Maryama; Ouafae, Benkhnigue; Hachi, Touria; Mohamed, El Bouhaddioui; Imane, Bouabadi; Atmane, Rochdi; Zidane, Lahcen (Lazaroa, 2016)
An ethnobotanical survey of medicinal plants was carried out in the Central Middle Atlas in the years 2013 and 2014 to establish the catalog of medicinal plants used in traditional medicine in the treatment of diabetes. Thus, 1560 people were interviewed, using questionnaires. The latter enabled us to gather information on traditional healing practices of the local population including scientific name, French name, vernacular name, plant parts used , therapeutic indications , revenues and mode of administration. The results show that 76 medicinal species were inventoried in the study area. These plant species are included into 67 genus and 40 families. The most represented families are: Lamiaceae (12 species), Asteraceae and Brassicaceae species with 14 each. Of 76 medicinal species found in the region, four species are reported for the first time in the traditional treatment of diabetes in Morocco. They are Pistacia atlantica, Ptychotis verticillata, Anacyclus pyrethrum, Alyssum spinosum, Cistus albidus, Juniperus thurifera, Ephedra nebrodensis, Thymus algeriensis, Th. munbyanus, Th. zygis, Abelmoschus esculentus, Fraxinus augustifolia, Sorghum vulgare and, Eriobotrya japonica. The leaves are the most used organs (38%). The decoction is the dominant mode of preparation (50%) and administration is mostly for oral use (97%).